Pertolongan Pertama pada Kecelakaan di Kamar Mandi - Siregar, Ayu Fitria; Usiono (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The toilet is a room that is usually messy and soaking wet. The bathroom functions primarily as a place to clean oneself, urinate and defecate. Therefore, maintaining the tidiness of the toilet is very important. The research method used is a qualitative research method with the data source used in the form of secondary data obtained from several international journals and articles. The Center for Disease Control and Prevention reports that every year, accidents in the bathroom cause 235 thousand people aged over 15 years were rushed to the Emergency Unit, and 14% of them ended up in hospital.benefits gained from keeping the restroom clean. one of them is for body health. Having a healthy and strong body is everyone's dream. Therefore, it is important for us to maintain the health of ourselves, our families, and the people around us.